2005
DOI: 10.1016/j.mod.2005.05.002
|View full text |Cite
|
Sign up to set email alerts
|

emc has a role in dorsal appendage fate formation in Drosophila oogenesis

Abstract: extramacrochaetae (emc) functions during many developmental processes in Drosophila, such as sensory organ formation, sex determination, wing vein differentiation, regulation of eye photoreceptor differentiation, cell proliferation and development of the Malpighian tubules, trachea and muscles in the embryo. It encodes a Helix-Loop-Helix transcription factor that negatively regulates bHLH proteins. We show here that emc mRNA and protein are present throughout oogenesis in a dynamic expression pattern and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, epithelial FCs begin differentiating at stage 2, with progressive down-regulation of Fas3. Furthermore, studies that manipulate Notch activity late in oogenesis have demonstrated requirements for Notch signaling during FC migrations [114][115][116], when epithelial FCs reactivate expression of early, 'immature' markers such as Fas3 [111], and Emc [112]. Thus, a nuanced model for dynamic modulations in Notch activity throughout FC morphogenesis is more appropriate.…”
Section: Maturation Of Epithelial Follicle Cellsmentioning
confidence: 99%
“…However, epithelial FCs begin differentiating at stage 2, with progressive down-regulation of Fas3. Furthermore, studies that manipulate Notch activity late in oogenesis have demonstrated requirements for Notch signaling during FC migrations [114][115][116], when epithelial FCs reactivate expression of early, 'immature' markers such as Fas3 [111], and Emc [112]. Thus, a nuanced model for dynamic modulations in Notch activity throughout FC morphogenesis is more appropriate.…”
Section: Maturation Of Epithelial Follicle Cellsmentioning
confidence: 99%
“…Localization of the br expression is also violated in the emc mutants, characterized by an ectopic emc expression. However, it is known that the br expression during the early and middle stages of oogenesis does not depend on the violation of the emc expression (Papadia et al, 2005); therefore, indirect influence of the EMC on the br expression by means of the mediator proteins is assumed. It is possible that the br unites not only the EGFR, DPP, and N but also other pathways in a single gene network.…”
Section: Gene Network Of Development Of Dorsal Appendagesmentioning
confidence: 99%
“…The emc was previously described as a gene that interacts with the N signal pathway. But also data exist that localization of the emc expression is controlled by the EGFR pathway, since violation of the emc expression pattern is observed in the mutants for the grk, fs(1)K10, and egfr genes (Cam puzano, 2001;Papadia et al, 2005). However, at the moment it is impossible to make definite conclusions about the activator or suppressor character of this interaction, and detection of additional components which participate in this interaction is required.…”
Section: Gene Network Of Development Of Dorsal Appendagesmentioning
confidence: 99%
“…The construction of the eggshell (chorion) by the Drosophila ovarian follicle cells is emerging as a powerful model system in which to study tubulogenesis and ECM patterning (Tzolovsky et al 1999;Berg 2005;Papadia et al 2005;Kleve et al 2006). The follicle cell epithelium surrounds the developing oocyte (see Figure 2, C and D) and in the absence of cell division synthesizes a multilayer ECM with a number of specialized features (see Figure 3, B and F).…”
mentioning
confidence: 99%